AUGMENTED REALITY AFFECTS STUDENTS’ ATTITUDE AND CONCEPTUAL UNDERSTANDING IN LEARNING 3D GEOMETRY - Auliya, Risma Nurul; Munasiah, Munasiah (Jurnal Pendidikan Indonesia, 2020)
The study investigates the impact of using AR in learning 3D geometry on students’ attitudes and conceptual understanding. The research was carried out using a quasi-experimental design, in particular by using a conceptual understanding test and attitude towards geometry questionnaire, in a public secondary school in Rangkasbitung, Banten, Indonesia. Two groups of students were used for data collection; the experimental (31 students) and the control groups (30 students). The data analyzed by independent sample t-test, using a significant level of 0.05. The results of this study were: (1) students’ conceptual understanding in mathematics in AR group was better than the control group, (2) students’ conceptual understanding in mathematics for both groups was in the medium category, and (3) students’ attitude towards geometry in AR group was better than the control group. Therefore, the appropriate method that is used in learning geometry can affect students’ conceptual understanding and attitude towards geometry. Additionally, the learning environment also needs to be teachers’ attention, because it can affect students’ involvement in the learning process.